Phylogenetic relationships, population genetics and hybridisation of two species of southern fur seal (Arctocephalus spp.) - Wynen, LP (2002)
This research investigated the phylogenetic relationships and population genetics of two species of fur seal in order to provide a basis for the study of the hybridisation of these species at Macquarie Island. The Antarctic (Arctocephalus gaze/la) and subantarctic fur seals (Arctocepha/us tropicalis) occur throughout the subantarctic region of the Southern Ocean, hauling out on remote islands throughout the region to breed. Both species were subject to intense sealing activities in the 18th and 19th centuries. The competitive and indiscriminate nature of the industry ensured that all populations were greatly reduced in size, with some becoming extinct. The cessation of sealing in the early 20th century has allowed both species to recover in number, and recolonise islands across their former range. The current range for the Antarctic fur seal overlaps with that of the subantarctic fur seal at lies Crozet, Marion Island and Macquarie Island. Hybridisation has been reported at low levels at Marion Island, and at higher levels at Macquarie Island. The situation at Macquarie Island is further complicated by the presence of an additional species, the New Zealand fur seal (Arctocephalus forsteri) While this species is not breeding on the island, some males participate in the breeding process, with some hybrids being produced This research seeks to apply molecular methods to investigate the hybridisation that is occurring at Macquarie Island within the context of the evolutionary and recent history of the two breeding fur seal species, and to a lesser extent, the New Zealand fur seal. The phylogenetic relationships of the Antarctic and subantarctic fur seals were investigated within the context of the family Otariidae. This family include the nine species of fur seal (Genera Arctocephalus and Callorhinus), and five species of sea lion (Genera Neophoca, Phocarctos, Eumetopias, Zalophus, and Otaria). A 360 base pair region of the cytochrome b gene in the maternally inherited mitochondrial genome was used for the primary ...